Analysis of the desertification dynamics of sandy lands in Northern China over the period 2000–2017. Issue 17 (21st September 2021) - Gou, Fen; Liang, Wei; Sun, Shaobo; Jin, Zhao; Zhang, Weibin; Yan, Jianwu
Abstract: It is of great practical significance to thoroughly study the environmental changes and conduct desertification assessments of sandy lands to elucidate the formation and recovery mechanism of desertification. The purpose of this study is to evaluate the desertification process and its driving factors accurately and objectively, and compare the differences of desertification process in different areas. We used Moderate Resolution Imaging Spectroradiometer (MODIS) surface albedo (MCD43A3) and leaf area index (LAI) (MCD15A2H) products to calculate the desertification divided index (DDI) to reveal the spatial-temporal variation regularity of the four sandy lands in northern China during 2000–2017 as well as the correlation between desertification and precipitation. The results showed that the total desertification degree of sandy lands in northern China showed a downward trend during the study period. By grading the desertification level, it was found the decline trend of severe desertification and high desertification was relatively significant ( p < 0.05). The spatial trend of the desertification level in sandy lands was significantly different, and the decreased area of severe desertification and high desertification in Mu Us sandy land was the largest (−0.042 × 10 4 km 2 yr −1 and −0.052 × 10 4 km 2 yr −1 ), while the interannual variation of the various desertification levels in Hulun Buir sandy land was small (±0.003 × 10 4 km 2 yr −1 ). The precipitation and DDI were positively correlated in most areas ( p < 0.05). Especially in Mu Us sandy land and Hunshandake sandy land, the proportional area of positive correlation between the precipitation and DDI was more prominent, accounting for 72.9% and 63.7%, respectively. This study had important decision-making significance for the effective management of sandy lands in arid/semiarid areas.